Geochemical characteristics and source analysis of crude oil from Archean buried hill JZ25-1S in Liaoxi Low Uplift - Tingting ZHAO; Xiaoping LUO; Piao WU; Yunlong XU; Jian LUO; Yanxu SUN (Shiyou shiyan dizhi, 2020)
The physical properties, group composition, stable carbon isotope, and biomarker compound distribution characteristics of crude oil in the Archean buried hill were studied and compared with the geochemical characteristics of Paleogene crude oil, in order to discuss the geochemical characteristics and sources of crude oil from the Archean buried hill JZ25-1S in the Liaoxi Low Uplift. The crude oil from the second member of the Paleogene Shahejie Formation and the Archean buried hill in this area are mainly light and medium crude oil. The oil has medium saturated hydrocarbon, high aromatic hydrocarbon, high non-hydrocarbon and asphaltene contents. The carbon isotopes of the crude oil are distributed between -26.2‰ and -24.4‰, and the isotopic fractionation among group components is small. The chromatographic curve clearly shows the "bulge" formed by biodegradation, the single peak and post-kurtosis state is dominant, the Pr/Ph value is generally around 1.3, and the Pr/nC17, Ph/nC18 values are both high. The sterane characteristics of crude oil show a high gammacerane abundance, the C27 rearranged sterane and 4-methyl sterane contents are medium, the dinostane content is low, and the regular sterane C27, C28, C29 fingerprints are partial"V" or "L" shaped. However, the characteristics of Archean crude oil from wells JZ25-1S-4D and JZ25-1-10D are quite different from the above-mentioned crude oil. Comprehensive analysis suggests that the main body of crude oil from the Paleogene and Archean buried hills in the JZ25-1S area is a mixture from the Es3 member of the Liaoxi Sag and the Es1 member of the Liaozhong Sag. Its parent material comes from a weakly reducing environment with moderate salinity and is mainly derived from algae and other phytoplankton. The crude oil has a high degree of maturity and is severely biodegraded. The Archean buried hill crude oil from wells JZ25-1S-4D and JZ25-1-10D is derived from the Es3 member source rock in the Liaoxi Sag, which was deposited in a weakly reducing freshwater environment with high maturity and weak biodegradation.